Consciência fonológica na alfabetização: proposta de material didático em inglês para 2º e 3º anos do ensino fundamental - Rosa, Daniela Dala (2025)
This exploratory research (Gil, 2021) deals with phonological awareness in the Portuguese/English literacy process for students in the 2nd and 3rd years of Elementary School, as well as presents a proposal for teaching material in English as an Additional Language (AL). The present study is focused on the development of graphophonological awareness skills, that occur at the level of Alphabetic Literacy, according to the Four Levels of Literacy Model (Alves; Finger; Brentano, 2021). In addition, it is based on the theoretical contributions of Silva (2012) about the linguistic systems of the Portuguese and English Languages; Soares (2016) about literacy; and Lamprecth (2012) about sound awareness. To prepare teaching materials, we seek to use the theoretical-methodological precepts of Sociodiscursive Interactionism (ISD - Bronckart, 2009), more specifically of Language Didactics (Dolz; Noverraz; Schneuwly, 2004, Denardi, 2009), which adopts the conception of language as a social practice, besides the teachings of Leffa (2008) and Tomlinson (2016) on the development of teaching materials in the English language. Considering that there are few teaching materials, that prioritize the development of phonological awareness in English for children who are in the literacy phase in their mother tongue, Portuguese, the main objective of this work is to present a proposal of an English teaching material focused on the development of graphophonological skills for students of the 2nd and 3rd years of Elementary School, who are in the alphabetic literacy phase. Specifically, the study aims to: i) understand the theoretical-methodological process related to the construction of a didactic sequence; and ii) produce a didactic sequence around the literary genre poem. The didactic sequence around the poem genre is consistent with the didactic sequence model proposed by Dolz, Noverraz and Schneuwly (2004), presenting the following phases: presentation of the communication situation, first production, teaching modules, checklists, medial and final production. The implementation of the didatic sequence in the 2nd and/or 3rd years of elementary school, allows to evaluate the students’ learning in the formative and summative modalities. Furthermore, since the focus of the didactic sequence is on the development of graphophonological skills, the activities on rhymes, alliterations, and phonemes are varied and provided through the use of different teaching strategies/tools: songs, videos, listening activities, activities that promote playfulness (word searches, tongue twisters, etc.), as well as object production. It is believed that the proposed didactic sequence could contribute to the teaching and learning of English of children aged 8 to 10 years old, as well as to the English teacher education in and for children.